Ground State Solutions to a Coupled Nonlinear Logarithmic Hartree System (Journal of Partial Differential Equations, 2025)
In this paper, we study the following coupled nonlinear logarithmic Hartreesystemwhere $β,μ_i,λ_i$ ($i=1,2$) are positive constants, ∗ denotes the convolution in $\mathbb{R}^2.$ Byconsidering the constraint minimum problem on the Nehari manifold, we prove theexistence of ground state solutions for $β > 0$ large enough. Moreover, we also showthat every positive solution is radially symmetric and decays exponentially.